2014
DOI: 10.1021/ja5060884
|View full text |Cite
|
Sign up to set email alerts
|

Bis(imino)pyridine Cobalt-Catalyzed Dehydrogenative Silylation of Alkenes: Scope, Mechanism, and Origins of Selective Allylsilane Formation

Abstract: The aryl-substituted bis(imino)pyridine cobalt methyl complex, ((Mes)PDI)CoCH3 ((Mes)PDI = 2,6-(2,4,6-Me3C6H2-N═CMe)2C5H3N), promotes the catalytic dehydrogenative silylation of linear α-olefins to selectively form the corresponding allylsilanes with commercially relevant tertiary silanes such as (Me3SiO)2MeSiH and (EtO)3SiH. Dehydrogenative silylation of internal olefins such as cis- and trans-4-octene also exclusively produces the allylsilane with the silicon located at the terminus of the hydrocarbon chain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
171
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(180 citation statements)
references
References 60 publications
9
171
0
Order By: Relevance
“…However, the observed main silylated compound for this catalyst was unsaturated allylic triethyl(2‐octen‐1‐yl)silane ( 6 ), with 60 % selectivity; this fact indicates that the main catalytic reaction occurring is a tandem isomerization–dehydrogenative silylation (Scheme b). As expected, 6 consisted of a 3:1 mixture of E / Z isomers . In all cases, the silylation products obtained were selectively anti ‐Markovnikov.…”
Section: Figuresupporting
confidence: 75%
See 1 more Smart Citation
“…However, the observed main silylated compound for this catalyst was unsaturated allylic triethyl(2‐octen‐1‐yl)silane ( 6 ), with 60 % selectivity; this fact indicates that the main catalytic reaction occurring is a tandem isomerization–dehydrogenative silylation (Scheme b). As expected, 6 consisted of a 3:1 mixture of E / Z isomers . In all cases, the silylation products obtained were selectively anti ‐Markovnikov.…”
Section: Figuresupporting
confidence: 75%
“…Upon using hexenes, similar conversions were attained; however, the ratio of vinylsilanes increased and reached 7, 16, and 14 % of the product mixture in the reactions of trans ‐3‐hexene, trans ‐2‐hexene, and 1‐hexene, respectively (see the Supporting Information). The longer chain in the octanes might explain the higher percentage of allylsilane, as steric repulsion would lead towards selective β‐hydride elimination in the reaction intermediate . Higher amounts of dehydrogenative silylation products were reached, from which 8 was the main species.…”
Section: Figurementioning
confidence: 99%
“…[3a,20] Recently,a nalogous tandem isomerization/hydroboration of internal alkenes was developed. [22] However,t here are few prior reports of basemetal-catalyzed isomerization/hydrosilylation reactions. [22] However,t here are few prior reports of basemetal-catalyzed isomerization/hydrosilylation reactions.…”
mentioning
confidence: 99%
“…Again the Chirik group demonstrated that a rational catalyst design allows to control the selectivity of a given reaction (Scheme ) . While the aryl‐substituted bis(imino)pyridine cobalt methyl complex 26 b promoted the catalytic dehydrogenative silylation (DHS) of linear α‐olefins to the corresponding allylsilanes (DHS/HS=100:0), the N‐methyl‐substituted and the cyclic bis(imino)pyridine cobalt complexes 44 and 45 resulted in high hydrosilylation (HS) selectivity (>98 %) affording 95–98 % product yields . Here, the coordination of the carboxylate ligand to the cobalt centre in 44 and 45 improved the bench stability of complexes with undiminished high activity.…”
Section: Catalytic Reductionmentioning
confidence: 99%